EFEKTIVITAS STRATEGI HEURISTIK DENGAN PENDEKATAN METAKOGNITIF DAN PENDEKATAN INVESTIGASI TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA PADA MATERI POKOK BARISAN DAN DERET DITINJAU DARI KREATIVITAS SISWA KELAS XII MADRASAH ALIYAH DI PONTIANAK - Yudi Darma; Imam Sujadi (Journal of Mathematics and Mathematics Education, 2011)
Abstract: The purposes of this research are to know of the effectiveness of heuristic learning strategy approach category, creativity, and its interaction to studentss mathematics problem solving ability on material series and sequence. This research is quasi experimental research with factorial design 2 x 3. The population is the studentss of class XII Madrasah Aliyah at Pontianak City the schools odd semester academic year of 2011/2012. The sampling was taken by using stratified cluster random. Sample of the research is 186 studentss. Data collecting is done through school document, problem solving essay test ability and creativity questionnaire. Instrument analysis that was done on essays problem solving ability is content validity, consist of analysis degree of differences, index of difficulty and reliability. Analysis on creativity questionnaire is content validity, internal consistency, and reliability. Data analysis technique used consisting of: Balance test, precondition analysis (Normality and Homogeneity). Hypothesis analysis test used was two way analysis of variance with unequal cell. Using α = 0.05 it can be concluded that: 1) Students who had been taught by using metacognitive learning approach result the better mathematics problem solving ability compared to students who had been taught by using investigation learning approach. 2) Students who have high creativity has better problem solving ability than students that have medium and low creativity, and students that have medium creativity have better problem solving ability than students who have low creativity. 3) Students who were taught by using metacognitive and also investigation learning approach, who have high creativity have better problem solving ability than students with medium and low creativity, and students who have medium creativity have better problem solving ability than students who have low creativity. 4) On high creativity level category, students who were taught by metacognitive learning approach have better mathematics problem solving ability than studentss who were taught by using investigation learning approach. Meanwhile on medium and low creativity, students who were taught by using metacognitive learning approach have the same mathematics problem solving ability with studentss who were taught by using investigation approach.Key words: Heuristic strategy, Metacognitive, Investigation, Creativity and Problem  Solving.